2019
DOI: 10.3390/en12040738
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Impedance Spectroscopy as a New Tool for Studying Biodiesel Fuel Aging Processes

Abstract: Fatty acid methyl esters (FAME), which are presently the main component of biodiesel fuels, undergo relatively fast oxidation processes. This behavior prevents long term storage of this fuel. From laboratory practices, it transpires that even after a very short period of storage, the oxidative stability of the biodiesel exceeds the values required by European regulations. Therefore, the goal of this work was to devise a parameter (marker) allowing for fast and convenient identification of the chemical stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…On the other hand, biodiesel oil-oil complex system is unstable, the polarity between aggregates and solvent seems to be remarkable. This is in agreement with the work of Biernat et al [27] that showed the increase of the polarity of oxidized FAME (at 95 °C, oxygen flow rate of 3 L/h) by using Electrochemical Impedance Spectroscopy (EIS). It is noteworthy that since B0 formulation contains only paraffins, naphtenes and aromatics, so, it does not contain any oxygenated specie prior to oxidation, whereas biodiesel samples have a great amount of methyl esters as well as unsaturated molecules, both of which are known to favor the oxidation process.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, biodiesel oil-oil complex system is unstable, the polarity between aggregates and solvent seems to be remarkable. This is in agreement with the work of Biernat et al [27] that showed the increase of the polarity of oxidized FAME (at 95 °C, oxygen flow rate of 3 L/h) by using Electrochemical Impedance Spectroscopy (EIS). It is noteworthy that since B0 formulation contains only paraffins, naphtenes and aromatics, so, it does not contain any oxygenated specie prior to oxidation, whereas biodiesel samples have a great amount of methyl esters as well as unsaturated molecules, both of which are known to favor the oxidation process.…”
Section: Discussionsupporting
confidence: 93%
“…Its popularity arises from its ability to conduct non-destructive analyses. In the context of biofuel analysis, EIS has emerged as a promising analytical tool for monitoring and evaluating the biodiesel and diesel-biodiesel blends [ 20 , 21 ] and aging processes of biodiesel fuel [ 22 ], and for assessing corrosion of metals in bioethanol-gasoline mixtures [ 23 ]. Most of the electrochemical cells used for this purpose are based on a capacitive system, which must have a large surface area and a short distance between the parallel plates of the capacitor to provide conditions for analyzing the dielectric constant of these mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In other hand, the literature about the research made in biodiesel is wide, and involves several aspects such as production, potential sources, oil extraction techniques, effects of fatty acid composition, characterization, diesel engine performance (7,8). The characterization of biodiesel involves many aspects, including the aging process (9), water content (10), dielectric properties (11) or the determination of antioxidants (12). These aspects define the quality of a biodiesel and there are different characterization techniques such as impedance spectroscopy (11,9) and voltammetry (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of biodiesel involves many aspects, including the aging process (9), water content (10), dielectric properties (11) or the determination of antioxidants (12). These aspects define the quality of a biodiesel and there are different characterization techniques such as impedance spectroscopy (11,9) and voltammetry (13,14). The characterization of the behavior of biodiesel in the engine is also widely studied, especially in the part of gas emissions (15,16) and performance (17,18,19).…”
Section: Introductionmentioning
confidence: 99%